Thermohaline staircase interface networking detection method resource, Arctic Ocean, 2024 ... - Lundberg, Michael (NSF Arctic Data Center, 2024)
The resource contains pseudocode and MATLAB code for the interface networking detection method (NDM). This method was used for systematic detection and specification of diffusive convective and salt fingering staircases in upper Arctic Ocean conductivity, temperature and depth (CTD) data. The method was developed over 2021-2024 for statistical analysis of staircase tendencies, seasonal variation, and regional disparities in the major Arctic Ocean basins and their over slopes. The changing upper Arctic Ocean hydrography, especially over the eastern side recently, has significant climate implications and correlates with changes in the staircase occurrence and properties. The method operated on data sets from profiler instruments belonging to the Nansen and Amundsen Basins Observational System (NABOS) project and Ice-Tethered Profiler (ITP) program. This data comprised of temperature and salinity profile records. The method employs a novel interface networking (graphing) process for extracting staircases from ...